2012
DOI: 10.1016/j.ejon.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The coping process of patients with cancer

Abstract: Purpose The aim of this study was to investigate the implications of the alterations to lifestyle of cancer patients, from the onset of abnormal symptoms, followed by diagnosis and treatment, and then subsequent acceptance of the condition. Seven cancer patients from medical centers in Taiwan participated in the study. Method Exploratory, qualitative study based on grounded theory methods. Each participated in a semistructured interview with open-ended questions. All interviews were audio recorded and transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 23 publications
9
43
0
7
Order By: Relevance
“…Consistent with previous studies, this study found that there were positive transition in women's lifestyles in term of their dietary habits and physical activity after breast cancer diagnosis (Salminen et al, 2000;Maunsell et al, 2002;Redhwan et al, 2008a;Chen and Chang, 2012). The most common changes were increments of physical activity and consumption of fruits and vegetable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, this study found that there were positive transition in women's lifestyles in term of their dietary habits and physical activity after breast cancer diagnosis (Salminen et al, 2000;Maunsell et al, 2002;Redhwan et al, 2008a;Chen and Chang, 2012). The most common changes were increments of physical activity and consumption of fruits and vegetable.…”
Section: Discussionsupporting
confidence: 89%
“…This attitude could create strained relationship with their husband. Similar thoughts among breast cancer women in previous studies at various places were pointed out in countries such as in Taiwan, Iran, England as well as Malaysia (Lindop and Cannon, 2001;Taleghani et al, 2008;Doumit et al, 2010b;McCann et al, 2011;Chen and Chang, 2012;Yusoff et al, 2012). Nevertheless, the women in this study were mostly young; 10 years younger than those in Western countries, hence special attention to this problem is warranted.…”
Section: Discussionsupporting
confidence: 77%
“…This period usually involves feelings of helplessness and panic for the patient. These results were consistent with many studies that suggested breast cancer survivors require emotional support (Helgeson and Cohen, 2000;Lu et al, 2010;Chen and Chang, 2012;Spiegel, 2012). Participants felt that they needed religion to lift their spirits, and they believe in the Buddhist "Karma" principles that people should do good for others.…”
Section: Discussionsupporting
confidence: 87%
“…A qualitative study that interviewed 14 newly diagnosed breast cancer patients reported that family support, seeking information about alternative information, practicing religion, attitude readjustment, and maintaining a normal lifestyle created a positive attitude for coping with cancer (Lu et al, 2010). A qualitative study of seven cancer patients found that the coping processes used by cancer sufferers enabled them to develop strategies and attitudes to assist them in living with cancer (Chen and Chang, 2012). Psychoneuroimmunology research has shown that stress modifies the delicate balance between health and disease (Tausk et al, 2008).…”
Section: Breast Cancer Survivors' Efforts To Renew and Preserve Theirmentioning
confidence: 99%
See 1 more Smart Citation